(untitled) (Ciudades, 2017)
The URBAN Community Initiative has been the main instrument for urban regeneration in the framework of regional policy of the European Union during the periods 1994-1999 and 2000-2006. The general objectives of this programme were related to the need to take measures against the loss of quality of life in certain parts of cities and to take action to promote the socioeconomic and environmental revitalisation of urban areas with difficulties. The action developed at Clichy-sous-Bois and Montfermeil (Île-de-France) will be used as an illustrative example of the type of interventions implemented and the impacts achieved by the URBAN CI. The commitment to an integrated approach of urban regeneration and the emphasis of the social dimension of the actions implemented are two of the key elements of the intervention model developed.